Augmenting ARMarkov-PFC predictive controller with PID-Type III to improve boost converter operation. (October 2018) - Anzehaee, Mohammad Mousavi; Behnam, Behzad; Hajihosseini, Payman
Abstract: The goal of this research is to improve the dynamic performance of a boost converter in continuous voltage mode controlled by a Type III PID controller. To this end, a special predictive controller called 'ARMarkov-PFC' has been used. In fact, in order to improve the performance of the closed-loop system during startup and reference input tracking and also enhance the relative stability of the system, the proposed controller has been augmented to this controller. Accordingly, a new controller namedA RMarkov-PFCP lusP ID (APP) has been proposed. Simulation and experimental results reveal that the proposed controller enjoys adequate performance and stability. Highlights: Boost Converter operation is improved in CCM using a controller without current sensor. An ARMarkov-PFC predictive controller is used to control boost converter. A hybrid controller of PID TypeIII and ARMarkov-PFC is introduced for boost converter.